2022
DOI: 10.36909/jer.15721
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Cut-Out Shape on the Dynamic Behavior of Composite Thin Circular Plates

Abstract: This study measures the impact of the cut-out shape on the fundamental frequency and the harmonic response of thin composite circular plates under fixed boundary conditions. For this purpose, the Finite Element Method has been employed using the SHELL181 element of ANSYS Workbench 18.2 software. Nine different circular plates having central equilateral triangle, square, regular pentagon, regular hexagon, regular heptagon, regular octagon, regular nonagon, regular decagon, and circular cut-outs have been design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Sun et al [17] conducted higher order free vibration study of elastic plates having multiple cutouts and observed that increase of skew angle of rhombic plate decreases the vibration frequency. Very recently, Das [18] studied the impact of cut-outs on circular plates and observed that presence of cut outs shifts the location of highest stress from edge towards middle of structure.…”
Section: Introductionmentioning
confidence: 99%
“…Sun et al [17] conducted higher order free vibration study of elastic plates having multiple cutouts and observed that increase of skew angle of rhombic plate decreases the vibration frequency. Very recently, Das [18] studied the impact of cut-outs on circular plates and observed that presence of cut outs shifts the location of highest stress from edge towards middle of structure.…”
Section: Introductionmentioning
confidence: 99%